Microbial populations, sensory, and volatile compounds profiling of local cooked rice - Mohammad Sabri, Nur-Shahera; Mahyudin, Nor Ainy; Abdullah Sani, Muhammad Shirwan; Han, Ming Gan; Chong, Kah Hui; Padmanabhan, Kousalya; Shan, Jiang; Mahmud Ab Rashid, Nor Khaizura (2023)
Objectives This study is designed to investigate the microbial populations, sensory, and volatile compounds profiling of locally cooked rice stored at room temperature (30 °C) on days 0, 1, 2, and 3 (D0, D1, D2, and D3) for the determination of specific spoilage organisms (SSOs).